Bergman theory induced by a quaternionic perturbed fractional ψ-Fueter operator - Cervantes, José O. González; Pérez de la Rosa, Marco A.; Bory Reyes, Juan (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 A useful tool proved in the present paper is the Borel–Pompeiu formula for the resulting function class of null solutions of the quaternionic perturbed fractional ψ-Fueter operator. Motivated by this formula, we developed major steps of the associated Bergman theory.